2014
DOI: 10.1038/bmt.2014.274
|View full text |Cite
|
Sign up to set email alerts
|

Presence of CD34+CD38−CD58− leukemia-propagating cells at diagnosis identifies patients at high risk of relapse with Ph chromosome-positive ALL after allo-hematopoietic SCT

Abstract: Relapse of Ph chromosome-positive ALL (Ph + ALL) results from the persistence of leukemia-propagating cells (LPCs). In Ph + ALL, a xenograft assay recently determined that LPCs are enriched in the CD34 + CD38 − CD58 − fraction. Therefore, the prognostic significance of LPCs in Ph + ALL subjects after allogeneic hematopoietic SCT (allo-HSCT) was investigated. A total of 80 consecutive adults with Ph + ALL who underwent allo-HSCT were eligible. A multi-parameter flow cytometry analysis examining CD58-FITC/ CD10-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In our study, 15 patients in a group of 80 patients with Ph(+) ALL after allo-hematopoietic stem cell transplantation had CD34 + CD38 − lymphoblasts in the first immunophenotypic examination. The authors showed that three months after bone marrow transplantation, an increase in the BCR/ABL transcript was observed in this group of 15 patients, which correlated with a high 3-year cumulative incidence of relapse and worse leukemia-free survival and overall survival ( 30 ). Similar conclusions are presented by Shram et al ( 31 ).…”
Section: Discussionmentioning
confidence: 94%
“…In our study, 15 patients in a group of 80 patients with Ph(+) ALL after allo-hematopoietic stem cell transplantation had CD34 + CD38 − lymphoblasts in the first immunophenotypic examination. The authors showed that three months after bone marrow transplantation, an increase in the BCR/ABL transcript was observed in this group of 15 patients, which correlated with a high 3-year cumulative incidence of relapse and worse leukemia-free survival and overall survival ( 30 ). Similar conclusions are presented by Shram et al ( 31 ).…”
Section: Discussionmentioning
confidence: 94%
“…We found inferior outcome and poor prognosis in the CD34+CD38−CD58− group compared with that in the other phenotype groups. In addition Kong et al [ 16 ] found that in a cohort of patients with allogenic bone marrow transplantation, the presence of CD34+CD38−CD58− LPCs correlated directly with higher 3-year cumulative incidence of relapse, and worse leukemia free-survival and OS.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these data, more recently, several papers reported that relapse of Philadephia chromosome positive ALL (Ph + ALL) patients is due to the persistence of leukemia-initiating cells (LICs), a self-renewing CD34 + CD38 − CD58 − population, capable of initiating human leukemia in immune-deficient mice (9497). Higher LICs frequencies at diagnosis are predictive of unfavorable prognosis and clinical outcome in AML (98100) and are considered an independent risk factor for relapse (101). This holds true also in childhood ALL, where a high proportion of CD34 + CD38 − cells negatively correlates with disease outcome and represents a useful marker for patients' risk stratification (102).…”
Section: Expression and Functional Role Of Ectonucleotidases In Hematmentioning
confidence: 99%